Peran Ukuran Perusahaan dalam Memoderasi Pengaruh Profitabilitas, Net Working Capital, dan Cash Flow terhadap Cash Holding pada Perusahaan Consumer Cyclicals di BEI Tahun 2019–2024 - Siska Arditasari; Fitri Susilowati; Ahsan Sumantika; Rini Armin (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
This study examines how profitability, net working capital, and cash flow influence corporate decisions in holding cash, with firm size as a factor that strengthens or weakens these relationships. The research focuses on consumer cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The study is motivated by economic recessions, including the Covid-19 pandemic, which significantly affected consumer purchasing power and corporate financial strategies. The research employs a quantitative approach using panel data regression analysis and Moderated Regression Analysis (MRA). The sample was selected based on specific criteria from companies in the consumer cyclicals sector. The findings reveal that profitability has no significant effect on cash holding. In contrast, net working capital and cash flow have a negative and significant effect, indicating that the higher these two factors, the less cash is retained by firms. Moreover, firm size strengthens the relationship between profitability, net working capital, and cash flow with cash holding. This study is expected to enrich academic understanding of cash management and provide practical insights for companies in formulating wiser and more adaptive cash management policies.